Vocational English Training for “Go Clean” Partners - Clara Herlina (Social Economics and Ecology International Journal (SEEIJ), 2019)
Nowadays, almost all people living in Jakarta use application for everyday needs, from transportation, buy food until cleaning houses. One of the companies that provide those services through online application is GOJEK. GOJEK offered a lot of services, such as GO Ride, GO Food, GO Massage and Go Clean. Go Clean is particularly giving service for cleaning houses or apartments and it has a lot of customers. Unfortunately, Go Clean partners often have to decline customers, particularly foreigners, because they are not able to converse in English. Thus, this community program is created to give training to Go Clean partners so that they will be able to conduct a simple conversation in English with foreign customers. The materials include introduction, parts of the house and price negotiation. After the training, it is expected that the workers will gain more customers and eventually it will increase their income.